Conference report SysMus 2016 - Diana Kayser; Jessica Akkermans; Pedro Douglass-Kirk (Music & Science, 2018)
Each year students from all over the world come together to share and discuss their knowledge on varying topics from the field of systematic musicology at the SysMus Conference. The 9th edition of this conference series, organised by students for students, took place in the idyllic town of Jyväskylä in Finland, and therefore for the first time in SysMus-history in one of the Nordic Countries. The 2016 conference was organised by student chairs Joshua Bamford and Susan Johnson with tremendous support from Birgitta Burger as supervising chair. With its international community and critically acclaimed researchers, SysMus 2016 proved to be a fruitful and exciting gathering.